PERTAMBANGAN BATU BARA: ANTARA MENDULANG RUPIAH DAN MENEBAR POTENSI KONFLIK - Robert Siburian (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2012)
In East Kalimantan, mining sector contributes more than three quarter of the provinces Gross Domestic Product. Given the high dependency on this sector, demand ? uctuation for mining products will have a signi? cant effect on the provincial economy. Since the decentralization era, mining activities, especially coal, have been increasing rapidly. Both the provincial and the district government have collected signi? cant income from the non-tax revenue. Despite the increased in the revenue, however, mining activities have not been able to improve the welfare of the communities. Even worse, there are widespread environmental damages in East Kalimantan due to reckless coal mining activities. In addition to this negative environmental impact, coal mining activities have also caused a series of con? ict both vertically and horizontally among communities. It coused some people to lose their land and their livelihoods. This paper examines coal mining activities in East Kalimantan and how it caused con? icts in the area. The study inds that there is a strong relationship between the forest, the land, and Dayak people, the indigenous people in this province. The forest and the land in East Kalimantan are used as a medium for showing peoples cultural identity. Without their forest and their land, Dayak people can not survive their cultural identity. Keywords: Pertambangan batu bara, kon? ik, orang Dayak, kerusakan lingkungan.